Mantle source to near-surface emplacement of enriched and intermediate poikilitic shergottites in Mars. (1st December 2019) - Rahib, Rachel R.; Udry, Arya; Howarth, Geoffrey H.; Gross, Juliane; Paquet, Marine; Combs, Logan M.; Laczniak, Dara L.; Day, James M.D.
Abstract: Poikilitic shergottites make up >20% of the current martian meteorite collection, with a total of 27 samples. These meteorites are intrusive gabbroic to lherzolitic rocks and represent igneous materials recording important processes in the martian crust. To further constrain petrogenetic relationships amongst enriched and intermediate poikilitic shergottites, we studied a comprehensive suite of poikilitic shergottites — including four newly recovered samples (Northwest Africa [NWA] 11065, NWA 11043, NWA 10961, NWA 10618) — using bulk rock major- and trace-element compositions, mineral major-element compositions, oxygen fugacity (ƒO2 ) values, crystallization temperatures, phosphorus maps of olivine grains, and quantitative textural analyses. The characteristic bimodal textures (poikilitic and non-poikilitic textures) of poikilitic shergottites record evolving magmatic conditions at different stages of crystallization. Higher temperatures and more reducing conditions during early-stage crystallization are recorded in the poikilitic textures, while lower temperature and more oxidizing conditions are recorded in the non-poikilitic textures during late-stage crystallization. Oxygen fugacity estimates relative to the quartz-fayalite-magnetite (QFM) buffer for early-stage olivine-pyroxene-spinel assemblages of enriched and intermediate poikilitic shergottites suggest decoupling of ƒO2 and the degree of light rare earth element (LREE)-enrichment (i.e., [La/Yb]CI ). An increase in ƒO2 exceeding 1 log unit from poikilitic to non-poikilitic textures implies degassing, with possible auto-oxidation, and/or crustal contamination. Quantitative textural analyses support the emplacement of both enriched and intermediate poikilitic shergottites as various shallow intrusive bodies, as well as a potentially widespread emplacement mechanism responsible for a major lithology of the martian crust. In addition, early assemblages (i.e., pyroxene oikocrysts) of all the poikilitic shergottites likely formed close to the crust-mantle boundary, implying a possible widespread presence of magma staging chambers at these depths. Fractional crystallization and magma storage in these chambers could have possibly resulted in all of the different enriched and intermediate shergottites that have been analyzed from Mars.